Decision Support System For Assessing The Performance Of The Best Posyandu Cadres Using The Weighted Product (WP) Method At The Tanjung Agung Palik Community Health Centre - Zevin Agustianza; Maryaningsih Maryaningsih; Venny Novita Sari (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The performance assessment of Posyandu cadres at the Tanjung Agung Palik Community Health Centreis still carried out manually, requiring a more measurable solution.This study aims to design and develop a Decision Support System(DSS) for assessing the performance of the best Posyandu cadres. This DSS was developedusing the Waterfall model and implementing the WeightedProduct (WP) method to process assessment data. The criteria usedinclude attendance, administration, length of service, and communication, which areweighted according to their level of importance. The application of the WP method involvescalculating preference vectors and normalising the final scores to producea ranking of cadres. The results show that this system is capable ofautomatically and efficiently presenting recommendations for the best cadres. It is hoped that this DSS can be an accurate and data-based tool, reducingsubjectivity and assisting health centres in making fair and accountable decisions.